ANALYSIS OF SURGICAL TREATMENT OF VENTRAL HERNIA FOR PATIENTS WITH OBESITY - Tashtemirova, Olga; Abitanova, Ainur; Zhusupov, Sabit (European Scientific Journal, ESJ, 2014)
The 65 patients with ventral hernia suffering obesity were examined. As a result of research the used methods of hernioplasty and complications in the early postoperative period were determined. The further results of surgical treatment were observed. The obtained data prove that application of non-tension methods of hernioplasty reduces the percent of complications and recurrences of hernia.